A Systematic Review With Network Meta-Analysis of the Available Biologic Therapies for Psoriatic Disease Domains - Torres, Tiago; Barcelos, Anabela; Filipe, Paulo; Fonseca, João Eurico (Frontiers in Medicine, 2021)
Several new treatments have been developed for psoriatic disease, an inflammatory condition that involves skin and joints. Notwithstanding, few studies have made direct comparisons between treatments and therefore it is difficult to select the ideal treatment for an individual patient. The aim of this systematic review with network meta-analysis (NMA) was to analyze available and approved biologic therapies for each domain of psoriatic disease: skin, peripheral arthritis, axial arthritis, enthesitis, dactylitis, and nail involvement. Data from randomized clinical trials (RCTs) were included. A systematic review was performed using MEDLINE database (July 2020) using PICO criteria. Bayesian NMA was conducted to compare the clinical efficacy of biological therapy in terms of the American College of Rheumatology criteria (ACR, 24 weeks) and Psoriasis Area and Severity Index (PASI, 10-16 weeks). Fifty-four RCTs were included in the systematic review. Due to the design of the RCTs, namely outcomes and time points, network meta-analysis was performed for skin and peripheral arthritis domains. For the skin domain, 30 studies reporting PASI100 were included. The peripheral arthritis domain was analyzed through ACR70 in 12 studies. From the therapies approved for both domains, secukinumab and ixekizumab were the ones with the highest probability of reaching the proposed outcomes. There is a lack of outcome uniformization in the dactylitis, enthesitis, and nails domains and therefore an objective comparison of the studies was not feasible. Nevertheless, secukinumab was the treatment with the best compromise between the number of studies in each domain and the results obtained in the different outcomes. Secukinumab and ixekizumab were the treatments with the highest probability of reaching both PASI100 and ACR70 outcomes. Due to the lack of a standard evaluation of outcomes of the other psoriatic disease domains, a network meta-analysis for all the domains was not possible to perform.